Cerebral Blood Flow Response to Simulated Hypovolemia in Essential Hypertension: A Magnetic Resonance Imaging Study. Issue 6 (December 2019) - Neumann, Sandra; Burchell, Amy E.; Rodrigues, Jonathan C.L.; Lawton, Christopher B.; Burden, Daniel; Underhill, Melissa; Kobetić, Matthew D.; Adams, Zoe H.; Brooks, Jonathan C.W.; Nightingale, Angus K.; Paton, Julian F. R.; Hamilton, Mark C.K.; et al.
Abstract : Hypertension is associated with raised cerebral vascular resistance and cerebrovascular remodeling. It is currently unclear whether the cerebral circulation can maintain cerebral blood flow (CBF) during reductions in cardiac output (CO) in hypertensive patients thereby avoiding hypoperfusion of the brain. We hypothesized that hypertension would impair the ability to effectively regulate CBF during simulated hypovolemia. In the present study, 39 participants (13 normotensive, 13 controlled, and 13 uncontrolled hypertensives; mean age±SD, 55±10 years) underwent lower body negative pressure (LBNP) at −20, −40, and −50 mmHg to decrease central blood volume. Phase-contrast MR angiography was used to measure flow in the basilar and internal carotid arteries, as well as the ascending aorta. CBF and CO decreased during LBNP ( P <0.0001). Heart rate increased during LBNP, reaching significance at −50 mmHg ( P <0.0001). There was no change in mean arterial pressure during LBNP ( P =0.3). All participants showed similar reductions in CBF ( P =0.3, between groups) and CO ( P =0.7, between groups) during LBNP. There was no difference in resting CBF between the groups ( P =0.36). In summary, during reductions in CO induced by hypovolemic stress, mean arterial pressure is maintained but CBF declines indicating that CBF is dependent on CO in middle-aged normotensive and hypertensive volunteers. Hypertension is not associated with impairments in the CBF response to reduced CO. Abstract : Supplemental Digital Content is available in the text.